THE EFFECT RECOMBINANT GROWTH HORMONE (rGH) DOSES BASED ON IMMERSION DURATION AND DIFFERENT AGE ON GROWTH AND SURVIVAL RATE OF TAMBAQUI LARVAE (Colossoma macropomum) - Rios Apriliyan Saputra; Netti Aryani; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis research was conducted on July - September 2021, at Fish Hatchery and Breeding Laboratory of Fishery and Marine Faculty of Riau University. The research aim is to determine the effect of Recombinant Growth Hormone (rGH) with optimal doses based on immersion duration and different age on growth and survival rate of freshwater pomfret fish larvae. The method used was Completely Randomized Design with 2 factors. The first factor was the immersion time with 4 levels, namely 0 minutes (P0), 30 minutes (P30), 60 minutes (P60) and 90 minutes (P90). The second factor is larvae age with 3 levels, namely 3 days (H3), 5 days (H5) and 7 days (H7). Larvae was kept for 40 days in an aquarium with a density of 2 fish/L. The findings showed that recombinant growth hormone (rGH) with different immersion time and larvae age affected the growth of absolute weight and length, specific growth rate, and also survival rate of freshwater pomfret fish larvae. The treatment of 60 minutes immersion time and 7 days of larvae age (P60H7) showed the highest growth, namely absolute weight 3.22 g, absolute length 5.81 cm, specific growth rate of 17.06%/day, and survival rate of 92%. The parameter of water quality during the research was 27.6-27.9°C, pH 6.4-7.4, dissolved oxygen 6.4-7.1 mg/L, ammonia 0.003-0.146 mg/L, and an alkalinity of 7 ,4-22.3 mg/L. Keywords : Immersion Duration, Different Age, Recombinant Growth Hormone,Colossoma macropomum, Growth, Survival Rate.